Characteristics of Organic Matter Released from Water Treatment Sludge in Water Treatment Facilities - Anggreini, Sri; Saputra, Ade Jaya; LQ Parulian Sanjaya S (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Water treatment sludge (WTS) generated from water treatment plants (WTPs) contains organic matter (OM) that may be released during storage prior to the dewatering process due to the influence of temperature and oxygen. The release of OM from WTS can deteriorate the quality of treated water if the dewatering effluent is recycled back into the WTP system. This study aims to investigate changes in the quality of OM in WTS during storage under varying temperatures (20°C and 40°C) and oxygen conditions (oxic and anoxic). The characteristics of released OM were evaluated by measuring dissolved organic carbon (DOC), ultraviolet absorbance at 260 nm (UV260), and fluorescence Excitation-Emission Matrix (EEM). The Specific UV Absorbance (SUVA) parameter was also calculated to assess the aromatic content of OM. The highest DOC concentration (4.94 mg/L) was observed under anoxic conditions at 40°C, which was 4.3 times higher than the lowest value found under oxic conditions at 20°C (1.14 mg/L). The highest UV260 absorbance (13.55 m⁻¹) and SUVA value (2.74 m⁻¹/(mg/L)) were also found under the anoxic 40°C condition, indicating a dominance of aromatic and humic-like substances formed during storage. EEM fluorescence analysis detected three main peaks representing protein-like, fulvic acid-like, and humic acid-like substances. Fulvic and humic acid-like substances were released more abundantly under anoxic conditions compared to protein-like substances. Differences in oxygen and temperature conditions play a significant role in determining the characteristics of OM released from WTS.